FUNCTIONAL AND STRUCTURAL-SEMANTIC CHARACTERISTICS OF THE CONSTITUENTS OF THE LEXICAL-SEMANTIC FIELD OF "EAR" IN ENGLISH LINGUISTICS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
Among the sensory organs, the ear performs one of the main functions - hearing. It allows a person to listen to the world, understand it, feel the environment and find his place. Also, the ear appears as a physical object of the human body, that is, an external organ with its own shape, size (pair) and hearing ability. A person begins to know the world from himself, that is, scientific research is carried out in the way of direct participation of a person himself. In this process, the names of the parts of the human body - "somatisms", the phraseological units in which they are involved, occupy an important place.